Transition towards energy generation from renewable sources in the People’s Republic of China - Brusiło, Paweł (Transformacja w stronę produkcji energii ze źródeł odnawialnych w Chińskiej Republice Ludowej w latach 2000-2019, 2019)
Over the last years, the People’s Republic of China has undergone through the complex energy transition. This process sparked off because renewable energy (RE) sources became a more profitable and effective alternative for fossil fuels, which environmental, social and economic costs turned out to be incommensurate with the benefits. The increasing importance of RE sources in Chinese electricity generation has its reflection in the energy mix – in 2019 over 26% of energy was produced from renewable energy sources. The following article includes a review of the most crucial changes in the energy transition process between 2000 and 2019. This paper also attempts to find the main reasons for the growing supply of energy sourced from RE sources. Electricity generation data, used in the study, present changes in the energy mix and showing examples of relevant infrastructural projects (i.e. the Three Gorges Dam in Hubei province) allows to take a broad view at the ongoing process of energy sources diversification in China
Ekonomia XXI Wieku = Economics of the 21st Century, 2019, Nr 2 (22), s. 85-97
Keywords: China; renewable energy sourcese; transition; Chiny; odnawialne źródła energii; transformacja